Bunuel wrote:

Is p + pz = p?

(1) p = 0

(2) z = 0

\(?\,\,\,\,:\,\,\,\,\,p\left( {1 + z} \right)\,\,\mathop = \limits^? \,\,p\)

\(\left( 1 \right)\,\,\,p = 0\,\,\,\,\, \Rightarrow \,\,\,\,\,\left\langle {{\text{YES}}} \right\rangle\)

\(\left( 2 \right)\,\,\,z = 0\,\,\,\,\, \Rightarrow \,\,\,\,\,\left\langle {{\text{YES}}} \right\rangle\)

This solution follows the notations and rationale taught in the GMATH method.

Regards,

Fabio.

_________________

Fabio Skilnik :: GMATH method creator (Math for the GMAT)

Our high-level "quant" preparation starts here: https://gmath.net